Slogovne značilnosti --- premolk --- Pinterjevega dialoga - Onič, Tomaž (Primerjalna književnost, 2016)
Halting dialogue is considered one of the main elements of Harold Pinter's style of writing that has become known as "Pinteresque." This paper examines the most salient features of Pinter's dramatic dialogue, illustrates it with the excerpts from his plays, and comments on the problems of its translatability into Slovenian.
Keywords: Pinter, Harold, 1930-2008; angleška dramatika; gledališče absurda; dramski dialog; literarni slog; premolk